Design of Lean Management and Control Model for Power Grid Material Bidding and Purchasing Process - Wenjun Chen, Jian Luo, Jin Yang, Xiaolin Du (Forest Chemicals Review, 2022)
Design a lean management and control model for the power grid material bidding and procurement process to meet the basic procurement business functions, and improve the lean management and control level of the power grid material bidding and procurement process through functions such as procurement resource management. The data layer collects data required for management and control through automatic collection and external import collection. The collected data is transmitted to the model method layer and stored in the data center and cloud space at the same time; the model method layer includes the power grid material agreement inventory demand prediction algorithm and power grid materials Various technologies such as bidding and purchasing decision-making, minimum path calculation, scheduling model, etc., provide technical support for the analysis of management and control functions such as material procurement, material warehousing and distribution at the management and control analysis layer. The analysis results of the management and control analysis layer use reports, curves and images through the decision support layer The way is displayed to the controller. Experimental results show that the model can effectively count the bidding requirements of power materials, and use the shortest path length to transport power grid materials, saving a lot of management and control costs for power companies.